Immune interactions and regulation with CD39+ extracellular vesicles from platelet concentrates - Delorme, Adèle Silane; Laguide, Alexandra; Tamagne, Marie; Pinheiro, Marion Klea; Cagnet, Léonie; Neyrinck-Leglantier, Deborah; Khelfa, Mehdi; Cleophax, Sabine; Pirenne, France; Vingert, Benoît (Frontiers in Immunology, 2024)
Introduction: CD39 plays an important role in the immunoregulation and inhibition of effector cells. It is expressed on immune cells, including Tregs, and on extracellular vesicles (EVs) budding from the plasma membrane. Platelet transfusion may induce alloimmunization against HLA-I antigens, leading to refractoriness to platelet transfusion with severe consequences for patients. Tregs may play a key role in determining whether alloimmunization occurs in patients with hematologic disorders. We hypothesized that CD39 + EVs might play an immunoregulatory role, particularly in the context of platelet transfusions in patients with hematologic disorders.Such alloimmunization leads to the production of alloantibodies and is sensitive to the regulatory action of CD39.We characterized CD39 + EVs in platelet concentrates by flow cytometry. The absolute numbers and cellular origins of CD39 + EVs were evaluated. We also performed functional tests to evaluate interactions with immune cells and their functions.We found that CD39 + EVs from platelet concentrates had an inhibitory phenotype that could be transferred to the immune cells with which they interacted: CD4 + and CD8 + T lymphocytes (TLs), dendritic cells, monocytes, and B lymphocytes (BLs). Moreover, the concentration of CD39 + EVs in platelet concentrates varied and was very high in 10% of concentrates. The number of these EVs present was determinant for EV-cell interactions.Finally, functional interactions were observed with BLs, CD4 + TLs and CD39 + EVs for immunoglobulin production and lymphoproliferation, with potential implications for the immunological management of patients.